Electrochemical characteristics of silicon coated graphite prepared by gas suspension spray method for anode material of lithium secondary batteries - Jeon, B.J.; Kang, S.W.; Lee, J.K. (KOREAN INST CHEM ENGINEERS, 2006)
Silicon-coated graphite particles were tested as anodes for lithium ion rechargeable batteries. The synthetic graphite particles were first coated with silicon precursor containing solution by gas suspension spray method and then calcined at heat treatment temperature at 500°C under hydrogen atmosphere. The silicon-coated graphite showed high specific capacity and good cycle performance due to the formation of amorphous silicon-carbon black composite layer on the surface of the graphite particles. It has stable structure under repeated volume expansion and contraction. The silicon-coated graphite still has high irreversible capacity due to the solid electrolyte interface (SEI) formation during the 1st cycle. However, the capacity loss could be lessened to a certain level by controlling the composition of the solvent mixture in the electrolyte.